Physical training and assessment in the special action services: problems and solutions - Șchiopu Costel-Gabriel; Popescu Veronica (Editura Univeristatii "Stefan cel Mare" din Suceava, 2023)
The activity of the police officers of the Special Actions Service requires constant sports training, long resistance to effort and thorough learning of self-defence and intervention techniques. Most of the employees of the Iasi Special Actions Service are fighters, but they also practice other sports activities, than those required in the mandatory physical training courses. The present study is part of a confirmatory - ameliorative research, carried out on a group of 145 people, employees of the special forces of the Special Action Services Iasi, Suceava, Botosani, Bacau, Vrancea and Bistrita-Nasaud through the application of a questionnaire -survey of 13 questions between October 2020 and September 2022. The methods used in the research included: analysis of specialized literature and relevant legislation, questionnaire-survey, mathematical-statistical method. In the present study, the results will refer to the opinions of the military personnel regarding the physical training process, evaluation and what are the fighters' preferences for sports activities. At the same time, by applying the questionnaire, we aimed to identify, from the perspective of the employees, what are the proposals for improving the process of physical training and sports at the level of the Special Action Services.